Communication strategies of ESL learners : Problem solving or message enhancing? - Ting, Su Hie (Universiti Malaysia Sarawak, UNIMAS, 2012)
This paper is based on a study ofthe use of communication strategies by adult second language learners of English when performing a discussion task. The study aims: (1) to describe the communication strategies used by L2 learners in an attempt to find out whether the strategies are used more for coping with breakdowns in communication or for enhancing the negotiation of shared meanings in an interaction; and (2) to determine whether strategy use and preference vary with the L2 learners' proficiency in English. The interactional data collected for this study are analysed for types of communication strategies based on approaches such as Tarone (1980) and Faerch and Kasper (1984). The analysis is validated through the participants' retrospection on their beliefs as to why they had behaved in the way they had at significant points of the interaction. The results of this study are discussed in the light of the relationship between the frequency of communicative disruption and communicative success. The findings on the role of communication strategies have implications on the accuracy-fluency emphasis in language learning